2019
DOI: 10.1007/s10509-019-3498-z
|View full text |Cite
|
Sign up to set email alerts
|

Particle acceleration of two general particles in the background of rotating Ayón-Beato-García black holes

Abstract: The rotating Ayón-Beato-García (ABG) black holes, apart from mass (M ) and rotation parameter (a), has an additional charge Q and encompassed the Kerr black hole as particular case when Q = 0. We demonstrate the ergoregions of rotating ABG black holes depend on both rotation parameter a and charge Q, and the area of the ergoregions increases with increase in the values of Q, when compared with the Kerr black hole and the extremal regular black hole changes with the value of Q. Banãdos, Silk and West (BSW) demo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…where r 0 is the distance from the black hole to the observer and θ 0 represents the inclination angle between the direction to observer and the rotation axis of the black hole. By using ( 28), ( 29), ( 30), (31), and (32), the celestial coordinates (35) transform into Equation (36) represents a direct relationship between the celestial coordinates (α, β) and the impact parameters (ξ, η). Every single photon that approaches the observer determines a point on the (α, β)-plane of the image, which can be visible with the help of telescope.…”
Section: Black Hole Shadowmentioning
confidence: 99%
See 1 more Smart Citation
“…where r 0 is the distance from the black hole to the observer and θ 0 represents the inclination angle between the direction to observer and the rotation axis of the black hole. By using ( 28), ( 29), ( 30), (31), and (32), the celestial coordinates (35) transform into Equation (36) represents a direct relationship between the celestial coordinates (α, β) and the impact parameters (ξ, η). Every single photon that approaches the observer determines a point on the (α, β)-plane of the image, which can be visible with the help of telescope.…”
Section: Black Hole Shadowmentioning
confidence: 99%
“…The authors in Refs. [27][28][29][30][31] demonstrated that the regular black holes can be considered as the particle accelerator. The quasinormal modes of test fields around the regular black holes has been discussed explicitly in [32].…”
Section: Introductionmentioning
confidence: 99%